Piezoelectric ceramic preparation method capable of directly obtaining piezoelectric property
By utilizing the difference in thermal expansion coefficients of the glass phase in piezoelectric ceramics to generate permanent compressive stress, piezoelectric performance is directly obtained and depolarization is avoided, and the problem in the prior art that polarization is required to obtain piezoelectric performance and easy depolarization is solved.
Patent Information
- Application Number
- CN202411673807.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-11-21
AI Technical Summary
Existing piezoelectric ceramics need to be polarized to obtain piezoelectric properties, and there is a possibility of depolarization, resulting in a degradation of performance.
The low-temperature glass phase was prepared by melt quenching method, and the liquid phase dispersion and high-energy ball milling were used to mix the glass phase with the BT-based powder evenly. By sintering the ceramics quickly, permanent compressive stress was generated by the difference in thermal expansion coefficients of the grain boundary glass phase, and piezoelectric properties were directly obtained by inducing the ferroelectric domain orientation.
It realizes that piezoelectric performance can be obtained directly without polarization, and avoids depolarization, improving the structural stability and performance reliability of ceramics.
Smart Images

Figure CN119751048A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the application field of lead-free piezoelectric ceramics, and in particular to a method for preparing piezoelectric ceramics for directly obtaining piezoelectric properties. Background Art
[0002] Lead zirconate titanate-based piezoelectric ceramics have almost monopolized the field of piezoelectric applications and are widely used in piezoelectric actuators and transducers. However, lead is highly toxic, making the development of lead-free piezoelectric materials urgent.
[0003] Barium titanate (BaTiO3, BT) is the earliest discovered piezoelectric ceramic. Its piezoelectric performance can be greatly improved by solid solution at the A and B sites and the introduction of defects. It is one of the candidate materials that are expected to replace lead-based piezoelectric materials. The present invention combines defect engineering and the addition of a Bi-based second component to appropriately reduce the sintering temperature, reduce the shrinkage compressive stress during the rapid cooling process, increase the sintering yield, and improve the piezoelectric performance of BT-based ceramics.
[0004] Piezoelectric ceramics are all polycrystalline materials, and piezoelectric properties can only be obtained through DC polarization, AC polarization, and pulse polarization, which requires expensive high-voltage polarization equipment and increases the number of steps in the preparation of piezoelectric materials. Piezoelectric materials have a Curie temperature, and the piezoelectric properties obtained by polarization will be depolarized due to external forces, temperature fields, etc., thereby losing the piezoelectric properties. Therefore, it is necessary to develop a method for preparing piezoelectric ceramics that can directly obtain piezoelectric properties without depolarization.
[0005] The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as acknowledging or suggesting in any form that the information constitutes the prior art known to those skilled in the art. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing piezoelectric ceramics that can directly obtain piezoelectric properties, thereby solving the technical problem that piezoelectric ceramics need to be polarized to obtain piezoelectric properties and may be depolarized.
[0007] The microstructure of polycrystalline piezoelectric ceramics is composed of grains and grain boundaries. The low melting point glass phase is pinned to the grain boundary, and the difference in thermal expansion coefficients between the grain boundary phase and the grain phase is used to generate compressive stress, which provides a method for inducing ferroelectric domain orientation to directly obtain piezoelectric properties. The present invention prepares a low-temperature glass phase by melt quenching, and evenly mixes the glass phase with the BT-based powder by liquid phase dispersion and high-energy ball milling. The ceramic is sintered by rapid firing and rapid cooling. The grain boundary glass phase shrinks due to the difference in thermal expansion coefficients to generate uniform compressive stress, which provides a new idea for preparing piezoelectric ceramics that directly obtain piezoelectric properties and will not be depolarized.
[0008] The above technical objectives of the present invention are achieved through the following technical solutions: A method for preparing a piezoelectric ceramic that directly obtains piezoelectric properties comprises the following steps: (1) BDTbT-CCdW was prepared by a solid phase reaction method, and the synthesized BDTbT-CCdW was ground into submicron powder using a colloid mill; (2) Preparation of glass powder BaASTB by containerless air suspension process; (3) Using a high-energy ball mill to mix BDTbT-CCdW powder and BaASTB glass powder evenly; (4) Prepare BT-based piezoelectric ceramics by rapid firing and rapid cooling.
[0009] The present invention prepares BDTbT-CCdW ceramics by rapid firing, and by rapid firing and rapid cooling, the glass phase BaASTB is pinned to the grain boundary, and by means of the difference in thermal expansion coefficient, the glass phase pinned to the grain boundary produces shrinkage permanent compressive stress, inducing piezoelectric properties, so that the BT-based ceramics can directly obtain piezoelectric properties without polarization and will not depolarize.
[0010] Specifically, during the sintering process of BDTbT-CCdW ceramic materials, the glass phase BaASTB is distributed on the grain boundaries, forming a "nail"-like effect that tightly binds the ceramic grains. The existence of this glass phase restricts the movement between the grain boundaries, so it is called the "pinning effect". The movement of the grain boundaries determines the mechanical and electrical properties of the ceramic to a certain extent, and pinning the grain boundaries can improve the structural stability of the ceramic. The glass phase BaASTB usually has a different thermal expansion coefficient from the matrix ceramic. During the rapid burning and rapid cooling process, due to this difference in thermal expansion, the volume change of the glass phase during cooling is inconsistent with that of the matrix ceramic, which leads to a "contraction mismatch" at the grain boundary. Since the expansion of the glass phase is relatively small or the contraction is large, the matrix ceramic will be subjected to an inward contraction stress at the grain boundary, which is called "permanent compressive stress". This permanent compressive stress caused by the pinning effect can inhibit the movement of the domain wall inside the grain. The movement of the domain wall is the key to the polarization or depolarization of piezoelectric ceramics. When the domain wall is fixed by permanent compressive stress, the spontaneous polarization direction inside the ceramic will be "frozen", so that the material will show piezoelectric properties without polarization treatment. This "frozen" polarization direction gives the material permanent piezoelectric properties.
[0011] Preferably, in step (1), the chemical formula of BDTbT-CCdW is (1-z)(Ba 1-x Dy x )(Tb y Ti 1-y )O3-zCa(Cd 0.5 W 0.5)O3, where x=0.025-0.075, y=0.025-0.1, z=0.025-0.125.
[0012] In the present invention, the doping amounts of yttrium (Dy) and terbium (Tb) are in the range of 0.025-0.075 and 0.025-0.1, which can finely control the lattice structure of the material to achieve the best piezoelectric performance. These concentrations of yttrium and terbium ions can introduce an appropriate amount of lattice distortion, thereby improving the piezoelectric constant and dielectric properties. Controlling the doping concentration range to low doping (2.5%-10%) helps to optimize the piezoelectric and dielectric properties of the material without destroying the original perovskite structure, and maintain good stability at high temperatures. The doping range of x and y stabilizes the lattice of the perovskite structure, which not only improves the piezoelectric performance, but also improves the structural stability of the material in a thermal environment. Ca(Cd 0.5 W 0.5 The addition of )O3 is controlled at 0.025-0.125, which enhances the grain boundary pinning effect and helps to reduce the sintering temperature of the material, so that dense ceramics can be obtained by sintering at a lower temperature. This component helps to promote the liquid phase sintering process, thereby reducing sintering time and energy consumption and saving production costs.
[0013] Preferably, in step (1), the fully dried analytically pure raw materials are accurately weighed according to the stoichiometric ratio, ground and mixed uniformly, and then calcined at 1300-1350° C. for 2 h; the calcined BDTbT-CCdW is crushed and ground with a colloid mill, the colloid mill speed is 4500 rpm, the water cooling pressure is 0.3 MPa, the wet three-stage grinding is performed, and the flow rate is 0.5 L / h, and submicron BDTbT-CCdW powder is obtained after drying.
[0014] Preferably, the analytically pure raw materials include BaCO3, Dy2O3, Tb4O7, TiO2, CaCO3, CdO and WO3 in a ratio of 2.5:5:24.5:3:0.5 (molar ratio).
[0015] Preferably, in step (2), the containerless gas levitation process is a unique method for synthesizing materials, the core purpose of which is to reduce impurity contamination by avoiding contact between the material and the container, thereby improving the purity and performance of the material. Specifically, this process has the following steps when synthesizing BaASTB glass powder: Raw material preparation and tableting: The pure raw materials are accurately weighed and analyzed according to the stoichiometric ratio. After grinding and mixing, the raw materials are pressed into small round tablets (such as 5mm in diameter and 3mm in thickness).
[0016] Preliminary calcination: calcine the disc at 1050℃ for 4h to ensure that the material is fully reacted and forms a certain crystalline phase structure.
[0017] Containerless gas suspension melting: The disc is suspended in the melting furnace by air flow. Oxygen is usually used to suspend the sample, which can avoid contact between the sample and the container wall and effectively reduce defects caused by contamination. The suspended disc is heated to 1500℃ and maintained for 5 minutes to completely melt it. After melting, the sample is quickly placed in an ice-water mixture to quench, so that BaASTB glass powder with a glass structure can be formed.
[0018] Drying: Finally, the quenched glass powder is dried to obtain the final BaASTB glass powder.
[0019] Preferably, in step (3), the mass ratio of BDTbT-CCdW powder and BaASTB glass powder is BaASTB:BDTbT-CCdW=1.5-3.5wt%. That is, the glass powder accounts for 1.5-3.5 mass percent of the ceramic powder. If the content of BaASTB is too high, the amount of glass phase in the ceramic matrix may be too much, resulting in the original perovskite structure being covered by too much glass phase, thereby changing the lattice structure of the ceramic matrix and affecting the overall performance of the ceramic material. The present invention selects a ratio range of 1.5-3.5wt%, which can obtain an effective pinning effect without introducing too much glass phase, thereby ensuring close bonding between grains.
[0020] Preferably, in step (3), zirconium oxide balls are used as grinding media, wet ball milling is performed, the speed of the high-energy ball mill is 800 rpm, and the ball milling time is 4 hours.
[0021] Preferably, in step (4), polyvinyl alcohol is added to the BDTbT-CCdW and BaASTB mixture obtained in step (3) to granulate and tablet, and the binder is removed at 600°C. The blank after binder removal is rapidly fired and rapidly cooled in an air atmosphere to prepare BT-based ceramics. The rapid firing temperature is 1475-1525°C and the rapid firing time is 60-90 minutes. After the rapid firing, the blank is rapidly cooled to room temperature. Permanent compressive stress is generated during the cooling process. This stress fixes the polarization direction of the crystal, so that the piezoelectric properties can be spontaneously generated without the need for external polarization treatment.
[0022] Polyvinyl alcohol (PVA) acts as a binder during the granulation and tableting process, allowing the mixture to be formed into uniform and dense particles, improving the compressibility of the mixture and the final molding effect. After debinding at 600°C, polyvinyl alcohol is fully removed, which makes the ceramic blank more dense and reduces the pores that may exist inside the material during the sintering process, thereby improving the overall density of the ceramic and helping to improve its mechanical strength and electrical properties.
[0023] The rapid firing and rapid cooling process can generate permanent compressive stress through thermal expansion differences. This compressive stress is applied to the grain boundaries of the ceramic during the cooling process, which helps to pin the grain boundaries, fix the polarization direction inside the crystal, and inhibit the movement of the domain wall. This fixed polarization direction is the spontaneous polarization direction, which makes the ceramic have piezoelectric properties without external polarization treatment, simplifying the subsequent processing steps.
[0024] By means of the above technical solution, the present invention has at least the following beneficial effects: Conventional piezoelectric ceramics usually need to be polarized (through an external strong electric field) to orient the polarization inside the material to obtain piezoelectric properties. However, when these domains encounter high temperatures or mechanical shocks, they may re-orient randomly, resulting in degradation of piezoelectric performance, which is called "depolarization". In the present invention, the permanent compressive stress formed by the grain boundary pinning effect makes it impossible for the domains to move easily, so that even if high temperatures or other external disturbances are encountered during use, the direction of polarization can be kept unchanged, thereby effectively avoiding the occurrence of depolarization.
[0025] The present invention adopts a container-free air suspension process. Due to the lack of container restrictions, the molten material can completely avoid the introduction of impurities, so that the purity of the glass powder is relatively high, and good uniformity and controllable structural characteristics can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 This is an impedance resonance diagram characterizing the electromechanical coupling coefficient in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0029] In the present invention, BDTbT-CCdW powder prepared by a solid phase reaction method and BaASTB glass powder prepared by a containerless air suspension process are uniformly mixed by a high-energy ball mill, and BT-based piezoelectric ceramics are prepared by rapid sintering and rapid cooling. During the rapid cooling process, the glass phase BaASTB is pinned to the grain boundary of the BT-based ceramic, shrinks to produce a persistent and uniform compressive stress, and induces piezoelectric properties, so that the BT-based ceramics can directly obtain piezoelectric properties without polarization and will not depolarize. The piezoelectric constant d of the piezoelectric ceramics prepared by the present invention is 33=238-252pC / N, electromechanical coupling coefficient K p =0.390-0.398.
[0030] Example 1 (1) Preparation of 0.95(Ba) by traditional solid phase reaction method 0.975 Dy 0.025 )(Tb 0.05 Ti 0.95 )O3-0.05Ca(Cd 0.5 W 0.5 )O3 (BDTbT-0.05CCdW), the specific steps are: accurately weigh the fully dried analytical pure BaCO3, Dy2O3, Tb4O7, TiO2, CaCO3, CdO, WO3 according to the stoichiometric ratio, mix them evenly, and calcine them at 1315℃ for 2h. The calcined BDTbT-0.05CCdW is crushed and ground with a colloid mill. The colloid mill has a speed of 4500rpm, a water cooling pressure of 0.3MPa, a wet three-stage grinding, and a flow rate of 0.5L / h. After drying, submicron BDTbT-0.05CCdW powder is obtained.
[0031] (2) BaASTB glass powder was prepared by a containerless air suspension process, specifically, the following steps: accurately weighing the fully dried analytical pure raw materials according to the stoichiometric ratio of 2.5BaSO4-5Al2O3-24.5SiO2-3TiO2-0.5B2O3, grinding and mixing them evenly, pressing them into discs with a diameter of 5 mm and a thickness of 3 mm, and calcining them at 1050°C for 4 hours. The calcined discs were melted by a containerless air suspension process at a melting temperature of 1500°C and a melting time of 5 minutes. After melting, they were quenched in an ice-water mixture and dried to obtain BaASTB glass powder.
[0032] (3) BT-based piezoelectric ceramics were prepared by rapid firing and rapid cooling. The specific steps were as follows: BDTbT-0.05CCdW powder and BaASTB glass powder were mixed evenly in a high-energy ball mill. The mass ratio of BDTbT-0.05CCdW powder and BaASTB glass powder was BaASTB:BDTbT-0.05CCdW = 2.5wt%. Zirconia balls were used as grinding media and wet ball milling was performed. The speed of the high-energy ball mill was 800rpm and the ball milling time was 4h. An appropriate amount of polyvinyl alcohol was added to the evenly mixed BDTbT-0.05CCdW and BaASTB to granulate and tablet. The binder was debonded at 600°C. The debonded blank was rapidly fired and rapidly cooled in an air atmosphere to prepare BT-based ceramics. The rapid firing temperature was 1500°C and the rapid firing time was 60min. After the rapid firing, the blank was rapidly cooled to room temperature to obtain BT-based ceramics. The piezoelectric constant d was measured. 33 =245pC / N, electromechanical coupling coefficient K p =0.394.
[0033] Example 2 (1) Preparation of 0.975(Ba) by solid phase reaction method 0.925 Dy 0.075 )(Tb 0.025 Ti 0.975 )O3-0.025Ca(Cd 0.5 W 0.5 )O3 (BDTbT-0.025CCdW), the specific steps are: accurately weigh the fully dried analytical pure BaCO3, Dy2O3, Tb4O7, TiO2, CaCO3, CdO, WO3 according to the stoichiometric ratio, mix them evenly, and calcine them at 1350℃ for 2h. The calcined BDTbT-0.025CCdW is crushed and ground with a colloid mill. The colloid mill has a speed of 4500rpm, a water cooling pressure of 0.3MPa, a wet three-stage grinding, and a flow rate of 0.5L / h. After drying, submicron BDTbT-0.025CCdW powder is obtained.
[0034] (2) BaASTB glass powder was prepared by a containerless air suspension process, specifically, the following steps: accurately weighing the fully dried analytical pure raw materials according to the stoichiometric ratio of 2.5BaSO4-5Al2O3-24.5SiO2-3TiO2-0.5B2O3, grinding and mixing them evenly, pressing them into discs with a diameter of 5 mm and a thickness of 3 mm, and calcining them at 1050°C for 4 hours. The calcined discs were melted by a containerless air suspension process at a melting temperature of 1500°C and a melting time of 5 minutes. After melting, they were quenched in an ice-water mixture and dried to obtain BaASTB glass powder.
[0035] (3) BT-based piezoelectric ceramics were prepared by rapid firing and rapid cooling. The specific steps were as follows: BDTbT-0.025CCdW powder and BaASTB glass powder were mixed evenly in a high-energy ball mill. The mass ratio of BDTbT-0.025CCdW powder and BaASTB glass powder was BaASTB:BDTbT-0.025CCdW = 1.5wt%. Zirconia balls were used as grinding media and wet ball milling was performed. The speed of the high-energy ball mill was 800rpm and the ball milling time was 4h. An appropriate amount of polyvinyl alcohol was added to the evenly mixed BDTbT-0.025CCdW and BaASTB to granulate and tablet. The binder was debonded at 600°C. The debonded blank was rapidly fired and rapidly cooled in an air atmosphere to prepare BT-based ceramics. The rapid firing temperature was 1525°C and the rapid firing time was 30min. After the rapid firing, the blank was rapidly cooled to room temperature to obtain BT-based ceramics. The piezoelectric constant d was measured. 33 =238pC / N, electromechanical coupling coefficient K p =0.390.
[0036] Example 3 (1) Preparation of 0.875 (Ba) by traditional solid phase reaction method0.95 Dy 0.05 )(Tb 0.1 Ti 0.9 )O3-0.125Ca(Cd 0.5 W 0.5 )O3 (BDTbT-0.125CCdW), the specific steps are: accurately weigh the fully dried analytical pure BaCO3, Dy2O3, Tb4O7, TiO2, CaCO3, CdO, WO3 according to the stoichiometric ratio, mix them evenly, and calcine them at 1300℃ for 2h. The calcined BDTbT-0.125CCdW is crushed and ground with a colloid mill. The colloid mill speed is 4500rpm, the water cooling pressure is 0.3MPa, the wet three-stage grinding is at a flow rate of 0.5L / h, and the submicron BDTbT-0.125CCdW powder is obtained after drying.
[0037] (2) BaASTB glass powder was prepared by a containerless air suspension process, specifically, the following steps: accurately weighing the fully dried analytical pure raw materials according to the stoichiometric ratio of 2.5BaSO4-5Al2O3-24.5SiO2-3TiO2-0.5B2O3, grinding and mixing them evenly, pressing them into discs with a diameter of 5 mm and a thickness of 3 mm, and calcining them at 1050°C for 4 hours. The calcined discs were melted by a containerless air suspension process at a melting temperature of 1500°C and a melting time of 5 minutes. After melting, they were quenched in an ice-water mixture and dried to obtain BaASTB glass powder.
[0038] (3) BT-based piezoelectric ceramics were prepared by rapid firing and rapid cooling. The specific steps were as follows: BDTbT-0.125CCdW powder and BaASTB glass powder were mixed evenly in a high-energy ball mill. The mass ratio of BDTbT-0.125CCdW powder and BaASTB glass powder was BaASTB:BDTbT-0.125CCdW = 3.5wt%. Zirconia balls were used as grinding media and wet ball milling was performed. The speed of the high-energy ball mill was 800rpm and the ball milling time was 4h. An appropriate amount of polyvinyl alcohol was added to the evenly mixed BDTbT-0.125CCdW and BaASTB to granulate and tablet. The binder was debonded at 600°C. The debonded blank was rapidly fired and rapidly cooled in an air atmosphere to prepare BT-based ceramics. The rapid firing temperature was 1475°C and the rapid firing time was 90min. After the rapid firing, the blank was rapidly cooled to room temperature to obtain BT-based ceramics. The piezoelectric constant d was measured. 33 =252pC / N, electromechanical coupling coefficient K p =0.398.
[0039] The application scope of the present invention is not limited to Dy, Tb doped barium titanate (Ba 1-x Dy x )(Tb y Ti 1-y)O3)based ceramics, and is also suitable for other rare earth element doped barium titanate ((Ba 1-x Re x )(Tb y Re¢ 1-y )O3)-based ceramics. Rare earth elements usually have similar electron shell structures, especially the 4f electron configurations of lanthanide rare earth elements are similar, so that they have similar chemical properties and lattice coordination effects in material doping. Therefore, the present invention can be applied to other rare earth doped systems to obtain piezoelectric ceramics that directly obtain piezoelectric properties without polarization and will not depolarize.
[0040] Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a piezoelectric ceramic that directly obtains piezoelectric properties, characterized in that: The steps are as follows: (1) BDTbT-CCdW was prepared by a solid phase reaction method, and the synthesized BDTbT-CCdW was ground into submicron powder using a colloid mill; (2) Preparation of glass powder BaASTB by containerless air suspension process; (3) Using a high-energy ball mill to mix BDTbT-CCdW powder and BaASTB glass powder evenly; (4) Prepare BT-based piezoelectric ceramics by rapid firing and rapid cooling.
2. A method for preparing a piezoelectric ceramic that directly obtains piezoelectric properties according to claim 1, characterized in that: In step (1), the chemical formula of BDTbT-CCdW is (1-z)(Ba 1-x Dy x )(Tb y Ti 1-y )O3-zCa(Cd 0.5 W 0.5 )O3, where x=0.025-0.075, y=0.025-0.1, z=0.025-0.
125.
3. A method for preparing a piezoelectric ceramic that directly obtains piezoelectric properties according to claim 2, characterized in that: In step (1), the fully dried analytically pure raw materials are accurately weighed according to the stoichiometric ratio, ground and mixed uniformly, and then calcined at 1300-1350° C. for 2 h; the calcined BDTbT-CCdW is crushed and ground with a colloid mill, the colloid mill speed is 4500 rpm, the water cooling pressure is 0.3 MPa, the wet three-stage grinding is performed, and the flow rate is 0.5 L / h, and submicron BDTbT-CCdW powder is obtained after drying.
4. The method for preparing a piezoelectric ceramic for directly obtaining piezoelectric properties according to claim 3, characterized in that: Analytically pure raw materials include BaCO3, Dy2O3, Tb4O7, TiO2, CaCO3, CdO and WO3.
5. The method for preparing a piezoelectric ceramic for directly obtaining piezoelectric properties according to claim 1, characterized in that: In step (2), BaASTB includes BaSO4, Al2O3, SiO2, TiO2 and B2O3 in a ratio of 2.5:5:24.5:3:0.5 (molar ratio).
6. The method for preparing a piezoelectric ceramic for directly obtaining piezoelectric properties according to claim 5, characterized in that: In step (2), the preparation method of the glass powder BaASTB is as follows: The fully dried analytical pure raw materials were accurately weighed according to the stoichiometric ratio, ground and mixed evenly, and then pressed into discs with a diameter of 5 mm and a thickness of 3 mm, and calcined at 1050°C for 4 hours; the calcined discs were melted by a containerless gas suspension process, with a melting temperature of 1500°C and a melting time of 5 minutes. After the melting was completed, they were quenched in an ice-water mixture and dried to obtain BaASTB glass powder.
7. The method for preparing a piezoelectric ceramic for directly obtaining piezoelectric properties according to claim 1, characterized in that: In step (3), the mass ratio of BDTbT-CCdW powder and BaASTB glass powder is: BaASTB:BDTbT-CCdW=1.5-3.5wt%.
8. The method for preparing a piezoelectric ceramic for directly obtaining piezoelectric properties according to claim 1, characterized in that: In step (3), zirconia balls are used as grinding media, wet ball milling is performed, the speed of the high-energy ball mill is 800 rpm, and the ball milling time is 4 hours.
9. The method for preparing a piezoelectric ceramic for directly obtaining piezoelectric properties according to claim 1, characterized in that: In step (4), polyvinyl alcohol is added to the BDTbT-CCdW and BaASTB mixture obtained in step (3) to make granules and tablets, and the mixture is debinded at 600°C. The debinded blank is rapidly fired and rapidly cooled in an air atmosphere to prepare BT-based ceramics. The rapid firing temperature is 1475-1525°C and the rapid firing time is 60-90 minutes. After the rapid firing, the blank is rapidly cooled to room temperature.
Citation Information
Patent Citations
Piezoelectric ceramic, method for producing the same, piezoelectric element, multilayer piezoelectric element, liquid ejection head, liquid ejecting apparatus, ultrasonic motor, optical device, vibrating apparatus, dust-removing apparatus, imaging apparatus, and electronic device
CN105939983A
PZT-Pb(Sb1 / 2Nb1 / 2) ternary system piezoelectric ceramic material as well as preparation method and application thereof
CN114075073A
Piezoelectric / electrostrictive porcelain composition and its application
CN1754858A
Manufacture of barium titanate semiconductor porcelain
JP1992196591A
Piezoelectric ceramic composition and piezoelectric element
JP2013155079A